Multiband Antenna Structures for Heterogeneous Wireless Systems with Improved Performance - Parkash, Davinder (My University, 2015)
ABSTRACT The field of wireless and mobile communication is growing at very fast rate covering many technical areas. With the recent progress and rapid increase in mobile terminals, the design of multiband antennas for small mobile terminals is acquiring great importance. Research on microstrip antenna systems has been a warm topic in current years due to the demands for compact and multiband antennas for next generation heterogeneous wireless communications systems. Wi-Fi/WLAN/WiMAX technologies are most rapidly growing area in the modern wireless communication. This provides greatly increased freedom and flexibility such that user can move around within a broad coverage area and still be connected to the network. There have been growing demands for broadband and multiband antenna with compact size. Devices having compact size internal antennas have appeared to fulfill this need. In this work, the multiband and compact size microstrip antenna has been proposed to cover operating bandwidth requirements of various wireless standards like Wi-Fi/WLAN/WiMAX and UWB. Analytical models provide a basic understanding of the operation of a patch antenna and they also provide approximate dimensions of a patch antenna for a targeted frequency without using numerical simulations. The objective of this thesis is to provide compact, efficient and multiband microstrip antenna designs for heterogeneous wireless communication devices. All these proposed designs contribute to the development of wireless devices for the fourth generation wireless communication systems. Theoretical analysis and simulation is performed by using IE3D simulator and a photolithography process is used for fabrication of the proposed antenna and prototype antenna is tested with help of vector network analyzer to validate the simulated results. The various antenna characteristics of all the proposed antennas like return loss, current distribution, gain, efficiency and radiation pattern has been analyzed and plotted. In this thesis, the five multiband antennas are proposed for heterogeneous wireless communication systems. In first design, the rectangular shaped multiband antenna embedded with ‘hash shaped slots’ has been proposed for WLAN/WiMAX applications. This design is modified by inserting I-shaped slot from the top of the patch to achieve three resonating modes with higher bandwidth. In third design, the design is composed of four vertical monopoles with CPW feed and defects in the ground plane have been used to achieve multi-band operation. In the fourth design, antenna based on rectangular shaped ring embedded with three inverted ‘S’ and inverted ‘C’ shaped strips is used to generates the multiband operation. In the fifth design, rectangular shaped ring antenna based on microstrip feed embedded with three vertical strips has been presented. All the proposed antennas provide multiband and wide operating bandwidth with relatively low profile to fulfil the objectives of my thesis and it is suitable for heterogeneous wireless communication systems.
Ph.D. (ECED)
Keywords: Multiband Antenna; WLAN; WiMAX; Monopoles